Assessing the impact of mental health and sleep patterns on chronic disease progression: a longitudinal perspective - Kumar Mire, Sanjay; Kumar Sahu, Kishor (Journal of Neonatal Surgery, 2025)
This longitudinal study aims to evaluate the influence of mental health and sleep patterns on the progression of chronic diseases, including cardiovascular conditions, diabetes, and obesity. Over a 10-year period, the study tracked the health and lifestyle behaviors of individuals from diverse demographic backgrounds. Participants' mental health status, including stress levels, anxiety, and depression, were assessed using validated psychological scales, while sleep quality and duration were monitored through both self-reported questionnaires and objective measures such as actigraphy. The progression of chronic diseases was tracked through medical records, biomarkers, and clinical assessments. The results indicate a significant correlation between poor mental health, insufficient or disrupted sleep, and accelerated chronic disease progression. Furthermore, the study highlights that individual who reported better mental health and consistent sleep patterns experienced slower disease progression and improved overall health outcomes. This research underscores the critical need for integrated mental health and sleep management strategies in the prevention and management of chronic conditions.